Utilization of Herbs as Therapy in the Treatment of Diabetic Foot Ulcers - Kharisma Pratama; Syahid Amrullah; Jaka Pradika; Cau Kim Jiu; Wuriani Wuriani; Usman Usman; Yenni Lukita; Gusti Jhoni Putra (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
The number of diabetic foot ulcer (DFU) sufferers increases from year to year. Many studies have been conducted to examine the appropriate therapy to overcome DFU. One type of therapy that has been widely studied is related to the use of herbal products in treating DFU. So that currently there are many scientific articles that inform about the efficacy of herbal products in accelerating wound healing both acute and chronic. The activity aimed to socialize the use of herbal products in the treatment of foot ulceration. This activity was carried out in February 2022 in collaboration with the Public Health Center of Sungai Raya District as a health service that oversees the location of the activity. The target population in this activity are those who have a history of diabetes mellitus or diabetic foot ulcers or have a family with diabetic foot ulcers. Participants who participated were given health education about the management of diabetic foot wounds and the use of herbal products in the treatment of diabetic foot wounds.